The moderator role of Emotional Intelligence in the associaction between neuroticism and aggression - Salguero-Noguera, José Martín; García-Sancho, Esperanza; Fernández-Berrocal, Pablo (My University, 2015)
Neuroticism has been proposed as a transdiagnostic vulnerability factor that is relevant to psychological disorders and it has been found to predict higher levels of aggression (Miller & Lynam, 2011). From the General Aggression Model (GAM; Anderson & Bushman, 2002), personality traits informs schema that people use to interpret events in their social lives and influence the emotional response to them. People with high neuroticism would perceive experiences as more troubling than they really are, increasing their negative emotional response and choosing maladaptive ways of coping, like aggression. On the other hand, recent studies have linked Emotional Intelligence (EI) with lower levels of aggression, suggesting that the ability to perceive, understand and manage emotions would be a protective factor of aggression. EI is, both theoretically and empirically, different from personality. Moreover, from the GAM, EI is possible to influence the way that emotions are processed. In this sense, it would be hypothesised that individuals with high neuroticism could be less likely to engage in aggressive behaviour if they also have higher levels of EI. In this study, we aimed to test this hypothesis in a sample of undergraduate students. Moderation analyses showed that individuals with high levels of neuroticism reported a more frequent use of aggressive behaviour mainly if they had lower levels of EI. Implications of the present findings for theory and intervention are discussed.
Keywords: Inteligencia emocional; Agresividad (Psicología); Emotional intelligence; Aggression; Moderation